Policies and strategies to retain and support the return of experienced GPs in direct patient care: the ReGROUP mixed-methods study - John L Campbell; Emily Fletcher; Gary Abel; Rob Anderson; Rupatharshini Chilvers; Sarah G Dean; Suzanne H Richards; Anna Sansom; Rohini Terry; Alex Aylward; Grant Fitzner; Mayam Gomez-Cano; et al. (National Institute for Health Research, 2019)
Background: UK general practice faces a workforce crisis, with general practitioner (GP) shortages, organisational change, substantial pressures across the whole health-care system and an ageing population with increasingly complex health needs. GPs require lengthy training, so retaining the existing workforce is urgent and important. Objectives: (1) To identify the key policies and strategies that might (i) facilitate the retention of experienced GPs in direct patient care or (ii) support the return of GPs following a career break. (2) To consider the feasibility of potentially implementing those policies and strategies. Design: This was a comprehensive, mixed-methods study. Setting: This study took place in primary care in England. Participants: General practitioners registered in south-west England were surveyed. Interviews were with purposively selected GPs and primary care stakeholders. A RAND/UCLA Appropriateness Method (RAM) panel comprised GP partners and GPs working in national stakeholder organisations. Stakeholder consultations included representatives from regional and national groups. Main outcome measures: Systematic review - factors affecting GPs' decisions to quit and to take career breaks. Survey - proportion of GPs likely to quit, to take career breaks or to reduce hours spent in patient care within 5 years of being surveyed. Interviews - themes relating to GPs' decision-making. RAM - a set of policies and strategies to support retention, assessed as 'appropriate' and 'feasible'. Predictive risk modelling - predictive model to identify practices in south-west England at risk of workforce undersupply within 5 years. Stakeholder consultation - comments and key actions regarding implementing emergent policies and strategies from the research. Results: Past research identified four job-related 'push' factors associated with leaving general practice: (1) workload, (2) job dissatisfaction, (3) work-related stress and (4) work-life balance. The survey, returned by 2248 out of 3370 GPs (67%) in the south-west of England, identified a high likelihood of quitting (37%), taking a career break (36%) or reducing hours (57%) within 5 years. Interviews highlighted three drivers of leaving general practice: (1) professional identity and value of the GP role, (2) fear and risk associated with service delivery and (3) career choices. The RAM panel deemed 24 out of 54 retention policies and strategies to be 'appropriate', with most also considered 'feasible', including identification of and targeted support for practices 'at risk' of workforce undersupply and the provision of formal career options for GPs wishing to undertake portfolio roles. Practices at highest risk of workforce undersupply within 5 years are those that have larger patient list sizes, employ more nurses, serve more deprived and younger populations, or have poor patient experience ratings. Actions for national organisations with an interest in workforce planning were identified. These included collection of data on the current scope of GPs' portfolio roles, and the need for formal career pathways for key primary care professionals, such as practice managers. Limitations: The survey, qualitative research and modelling were conducted in one UK region. The research took place within a rapidly changing policy environment, providing a challenge in informing emergent policy and practice. Conclusions: This research identifies the basis for current concerns regarding UK GP workforce capacity, drawing on experiences in south-west England. Policies and strategies identified by expert stakeholders after considering these findings are likely to be of relevance in addressing GP retention in the UK. Collaborative, multidisciplinary research partnerships should investigate the effects of rolling out some of the policies and strategies described in this report. Study registration: This study is registered as PROSPERO CRD42016033876 and UKCRN ID number 20700. Funding: The National Institute for Health Research Health Services and Delivery Research programme.